TRANSDISCIPLINARY CHALLENGES OF SUSTAINABLE CONSTRUCTION AND REAL ESTATE DEVELOPMENT IN VISEGRAD COUNTRIES - Daniela Spirkova; Koloman Ivanicka (European Scientific Journal, ESJ, 2013)
The Visegrad countries – the EU members - are the most advanced transition countries, yet they face the serious problems, such as the dependence on the energy sources from abroad. Similarlyas other European countries they are obliged to meet the goals of the European Union in the area of energy savings in future (document Europe 2020). The special measures have been undertaken bysome of the countries but the overall results were to this moment quite controversial. The most important challenges are:• High costs of the energy from the renewable sources in times of economic austerity,• Lack of innovation capacities,• inadequate funding of the research and development and the problems of transition to marketeconomy,• Low support for transformation of the energy sector towards the use of renewable resourcesby the society,• Need for additional investments into the power grids,• The growth of consumerism,• Urban sprawl combined with very liberal approach to urban planning and development,• The mainstream political attitudes concerned especially with growth of wealth but not withprotection of the environment and energy savings,• Difficulties of the implementation of the efficient energy savings measures in the housingsector because of low solvency of often aging population.The aim of the paper is the identification of barriers and the suggestions of possible policy changes that would help to overcome the present problems.